Potential Carbon Stocks in the Kasepuhan Karang Customary Area - Abdul Mukti; Mahawan Karuniasa (Jurnal Penelitian Pendidikan IPA, 2025)
Customary areas in Indonesia, including Kasepuhan Karang, play a crucial role in forest conservation and climate change mitigation. According to data from the Indigenous Territory Registration Agency (BRWA), the Kasepuhan Karang customary area covers 1.081 hectares, with land cover composition including primary dry forest, settlements, mixed dry agriculture, and rice fields. The methods used in this study include GIS analysis and remote sensing with high-resolution imagery from PlanetScope, as well as field data verification. This study aims to analyze the potential above-ground carbon stocks in the customary area of Kasepuhan Karang, Banten Province. The results show that the primary dry forest land cover has the highest biomass potential of 38.507 Mg and carbon stocks of 18.099 Mg C. The total carbon stocks in the Kasepuhan Karang customary area are 42.986 Mg C, with varying distribution across different land cover classes. Mixed dry agriculture, which dominates this area, also has significant biomass potential and carbon stocks. These findings emphasize the importance of sustainable land management to optimize carbon sequestration potential and support climate change mitigation.